Website Design for Kelirskin Product Reseller Registration using the Prototype Method - Thahir, Raisa Mutia; Pratama, Reza; Fami, Amata; Barus, Irma Rasita Gloria; Mindara, Gema Parasti (JoMMiT, 2024)
Online registration of resellers through a website has become a crucial strategy for many companies, including Kelirskin, to enhance business efficiency. This research proposes the development of a dedicated website for registering as a Kelirskin product reseller using a prototype method. With this method, an analysis of system requirements, modeling, and prototype development is conducted, incorporating various essential features such as login, registration, product management, shopping cart, and reseller management. The result is a prototype with a user-friendly interface and functionality tailored to the needs. In conclusion, digital reseller registration via a website using the prototype method has the potential to enhance business efficiency and competitiveness. Suggestions for further research include conducting trials with representative users and paying attention to user training and regular system maintenance to ensure smooth operation.